Dysmenorrhea And Quality of Life Among Medical and Nursing Students: A Cross- Sectional Study - Shewte, Mamta K; Sirpurkar, Manik S (National Journal of Community Medicine, 2016)
Background: Dysmenorrhoea may also affect the health-related quality of life (HRQoL) may be disrupted among adolescent women. This study was conducted to assess the prevalence of dysmenorrhoea and its impact on quality of life among medical and nursing students. Methodology: A cross sectional study conducted from November 2014 to January 2015 at Chirayu Medical College and Hospital in central India, among 311 medical and nursing students using a Health Survey Questionnaire from the Medical Outcomes Study Short Form-36 (SF-36) to determine the HRQoL(Health related Quality of Life) of the study subjects. Results: Total 311 study subjects were studied, among them 202 (64.95%) were MBBS & 109 (35.05%) were nursing students. The average age of the students was 19.9 ± 1.6 years. 91.63% study sub- jects were Hindu by religion. The overall prevalence of dysmenor- rhoea was found to be 72.02 % (n = 224). In those with dysmenor- rhoea the scores received from all the domains of HRQoL were lower. It was statistically significant using student t test. Conclusions: Dysmenorrhoea is a very common problem among adolescent girls; it affects their quality of life. HRQoL decreases with the increase in the severity of dysmenorrhoea.